The Implementation of Counseling Guidance Values in Households Based on the Story of Umar Bin Khattab RA in the Book Uqudulijain - Renaldy, Alif Fikri; Rofiq, Arif Ainur (Jurnal Pengabdian Nusantara, 2025)
This article explores the values of domestic counseling reflected in the story of Umar bin Khattab in Kitab Uqudulijain. Umar bin Khattab, one of the outstanding caliphs, is known for his decisive leadership, progressive legal and administrative reforms, and dedication in expanding the territory of Islam while upholding the principles of justice and the welfare of the people. In the context of the household, Umar set an example through the application of values such as fairness, responsibility, and honest communication. These values are in line with the principles of counseling guidance that prioritize emotional balance, wise decision-making, and maintenance of harmonious relationships. As a leader, Umar always listened to the aspirations of his people fairly, an attitude that can be applied in the family to create respectful relationships. Umar bin Khattab's example shows the importance of building a solid household foundation based on Islamic values. By integrating these principles, families can achieve harmony and happiness, while instilling strong moral values to the next generation.